Impatiens tianlinensis (Balsaminaceae), a new species from Guangxi, China - Zeng, Lei; Liu, Yan-Nan; Gogoi, Rajib; Zhang, Lin-Jing; Yu, Sheng-Xiang (Phytotaxa, 2015)
Impatiens tianlinensis S. X. Yu & L. J. Zhang, a new species of the Balsaminaceae from Cenwang Laoshan Mountain, Tianlin County, Guangxi Region, is described and illustrated. This species closely resembles I. apalophylla and I. clavigera var. auriculata in having racemose inflorescences, 4 lateral sepals, hammer-shaped capsules and ellipsoid seeds, but differs in having sessile glanduliferous petioles, few-flowered inflorescences, incurved spur, yellow lower sepal without reddish patches, yellowish petals and lower sepal, and acuminate dorsal petal apex. The molecular data, from nuclear ribosomal and plastid genes, as well as pollen characters also support that the species is new to science.